(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This scientific article is dedicated to the prospects of development, problems, and solutions related to green economy in the Republic of Uzbekistan. The article discusses the theoretical foundations of green economy, its differences from the traditional economy, and analyzes international experience. The process of Uzbekistan’s transition to a green economy is examined, along with the ongoing reforms, such as the use of renewable energy sources, increasing energy efficiency, and strategies aimed at ecological sustainability. The article also addresses the problems hindering the development of green economy, such as financial, technological, and human resource barriers, and offers solutions to overcome them. Transitioning to a green economy is presented as a key factor in ensuring the country’s economic, ecological, and social stability